Racial characteristics of human teeth with special emphasis on the Mongoloid dentition - Yaacob, Hashim; Nambiar, Phrabhakaran; Naidu, Murali D.K. (College of Pathologists, Academy of Medicine Malaysia, 1996)
Determining the racial affinity of an unknown individual from dentition for identification is indeed a difficult endeavour. However, there are certain dental characteristics which are predominant in certain racial groups and these contribute important indicators in the identification process. Inherited dental characteristics are modified by prenatal and postnatal environmental and nutritional conditions. They can also become less discernible due to admixture of the various races.